Opportunities for Direct Uses of Geothermal Energy in Türkiye - World Bank (Washington, DC : World Bank, 2022)
Türkiye has substantial geothermal potential, and the country’s government is committed to exploiting it, both for economic reasons and to meet its obligations as a signatory of the Paris Agreement on Climate Change. Türkiye has more than 400 known geothermal fields in 63 different provinces. The country’s total estimated geothermal potential is more than 60,000 megawatts thermal. Developing that potential could create more than 120,000 direct jobs, with ample opportunities for women’s participation. The Turkish government has set an ambitious goal of 11,150 MWt in direct uses of geothermal energy by 2025. Meeting that goal will require raising awareness, building capacity, ensuring a favorable regulatory environment, and increasing access to funding for both public and private entities.